Comparative private law 1998 Dale Hutchison, UCT - Rolla, Olaf (Centre for Law and Society, 2026)
In any major building project many parties are involved, and the various contractual and other legal relationships become complex and require careful analysis. 1 The legal rights and obligations of the building parties like the employer2; the main contractor3; the sub-contractors; the architect; the quantity surveyor; the clerk of works; and all the specialists depend on each other or at least can influence and affect each other. Often engineering and building works will overlap, intermingle, or are based on each other. The breach of contractual or delictual duties by one building party can have an essential impact on the economical legal interests of other parties connected with the construction project. Not only the contractual parties themselves but everyone who is involved in the building process is in danger to suffer damage. Hence, especially and typio/71y in the building industry third parties may suffer pure economic loss as a result of negligent acts of one party which is not bound by a building contract in relation to the person suffering damage. Because of the multi-party involvement in design and construction few of the involved parties are in contractual relationship with each other, and owners are tempted to recover repair costs and associated consequential losses by seeking to shift the responsibility on those who are insured or financially secure. Liability for negligent acts causing pure financial loss is generally a legal problem that plagues many legal systems.